Implementing Safety Management Systems in Aviation. - Stolzer, Alan J. (Ashgate studies in human factors for flight operations., 2011)
In their first book, Safety Management Systems in Aviation, Stolzer, Halford, and Goglia provided a strong theoretical framework for SMS, along with a brief discourse on SMS implementation. This follow-up book provides a very brief overview of SMS and offers significant guidance and best practices on implementing SMS programs. Very specific guidance is provided by industry experts from government, industry, academia, and consulting, who share their invaluable insights from first-hand experience of all aspects of effective SMS programs.